The Effect of Internship and Emotional Intelligence on Work Readiness Through Work Motivation as an Intervening Variable (Universitas Negeri Semarang, 2022)
The purpose of this study was to determine whether there is a positive and significant effect of industrial work practices (Prakerin) and emotional intelligence on work readiness through work motivation. The study population was all students of class XII Accounting and Finance of the SMKN 1 Demak academic year 2019/2020 with a total of 104 students. The sampling technique used the saturated sample. Methods of data collection used a questionnaire. The data analysis method used descriptive statistical analysis, path analysis and Sobel test. The results showed that industrial work practices (Prakerin), emotional intelligence had a positive and significant effect on work readiness, both directly and through work motivation. Based on the results of the study, it can be concluded that work motivation mediated the effect of industrial work practices (Prakerin) and emotional intelligence on students' work readiness. Suggestions to improve work readiness can be taken by following up on the prakerin program to suit the student's area of ​​expertise. Then improve students' mental and emotional well-being by growing students' self-confidence which is supported by providing motivation and information about the world of work.